The effect of room temperature pre-ageing on tensile and electrical properties of thermomechanically treated Al-Mg-Si alloy - Martinova Z.; Damgaliev D.; Hirsh M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A commercial Al - 0.62%Mg - 0.57%Si was thermomechanically treated (TMT). The TMT process included solution treatment, room temperature preageing, drawing (e=95%) and final ageing. The experimental data were proceeded statistically and mathematical models were derived for the alloy properties such as tensile strength, electrical conductivity and elongation of the wires during TMT. The models are used to find out the area of compromise optimal combination of the alloy properties. Higher final ageing temperature and time are required to design a TMT process for production of a long-term pre-aged wires. The influence of the room temperature preageing on the precipitation process during TMT is discussed.